Preparation method of nano chitin, prepared nano chitin and application

By using low-concentration organic acids to react with chitin powder, nano-chitin is prepared, and organic acids and chitin residues are recovered, which solves the environmental pollution problem of high-concentration acids in the existing technology and increases the total production and production of chitin. application potential.

CN119306857APending Publication Date: 2025-01-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310847169.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In the prior art, high concentrations of hydrochloric acid or sulfuric acid are often used in the preparation of nanochitin, which leads to environmental pollution, and the insolubleness of chitin limits its development and application.

Method used

Use low-concentration organic acids (such as toluenesulfonic acid, oxalic acid, maleic acid) to react with chitin powder to prepare nano-chitin, and reduce chitin loss and the environment by recycling organic acids, chitin nano-whiskers and solid residues pollute.

Benefits of technology

Nanochitin was successfully prepared, realizing the recovery and recycling of organic acids, reducing environmental pollution, and increasing the total output and application potential of chitin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004333157540000011
    Figure HDA0004333157540000011
  • Figure HDA0004333157540000021
    Figure HDA0004333157540000021
  • Figure HDA0004333157540000022
    Figure HDA0004333157540000022
Patent Text Reader

Abstract

The invention discloses a preparation method of nano chitin, the prepared nano chitin and application of the nano chitin. The nano chitin comprises chitin nanofibers and chitin nanowhiskers. Comprising the following steps: (1) mixing chitin powder with organic acid, reacting to obtain a mixed solution I, and centrifuging the mixed solution I to obtain an upper-layer liquid I and a lower-layer solid I; (2) mixing the lower-layer solid I obtained in the step (1) with water to obtain a mixed solution II, and performing dialysis and centrifugation to obtain an upper-layer liquid II and a lower-layer solid II; (3) performing layering treatment on the supernatant liquid II obtained in the step (2) to obtain a product containing the chitin nanowhiskers and a mixed solution III; (4) carrying out high-pressure homogenization treatment on the mixed solution III obtained in the step (3) to obtain a product containing chitin nanofibers; the mass ratio of the organic acid to the chitin powder is (0.6-1.8): 1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a method for preparing nano-chitosan, the prepared nano-chitosan and applications, and belongs to the field of nano-material preparation. Background Art

[0002] Chitosan is a green natural polymer material that can be used as a renewable biological resource. It has the advantages of being non-toxic, natural, degradable and biocompatible. Chitosan can be divided into three crystal forms: α, β and γ according to the arrangement of the molecular chains and the combination of hydrogen bonds. Among them, the α crystal form is the most common and stable configuration, with sugar chains arranged alternately in parallel, and has strong intermolecular and intramolecular hydrogen bonds. The β crystal form is arranged in parallel in the same direction, and the intermolecular hydrogen bonds are weak. The γ crystal form is composed of two sugar chains in the same direction and one sugar chain in the opposite direction arranged in parallel. Due to its highly ordered crystal structure, chitosan is insoluble in most common solvents. This insolubility seriously limits the development and application of chitosan. Nanochitoin (chitoin nanowhiskers and chitosan nanofibers) prepared from chitosan can form a stable and uniform dispersion in water. It not only has the properties of chitosan, but also has properties such as high aspect ratio, high surface area, and low density. The hydroxyl groups, acetyl groups, and residual amine groups on its surface can also be chemically modified. Therefore, it can be used for polymer reinforcement, food packaging, water treatment, and drug delivery.

[0003] At present, there are three methods for preparing nano-chitin: acid hydrolysis, mechanical treatment, and TEMPO oxidation. In acid hydrolysis, high-concentration hydrochloric acid and sulfuric acid are often used, which will cause certain pollution to the environment. Summary of the invention

[0004] Nano-chitin prepared by low-concentration organic acid used in this application can recycle organic acid after preparation to reduce pollution. Chitosan nano whiskers and CSR (chitosan solid residue) are recovered at the same time to minimize chitosan loss and increase total output. Wherein CSR (chitosan solid residue) can be converted into chitosan nanofibers by high-pressure homogenization. Waste acid can be recovered and recycled by methods such as recrystallization and rotary evaporation.

[0005] According to one aspect of the present application, a method for preparing nano-chitosan, wherein the nano-chitosan includes chitosan nanofibers and chitosan nanowhiskers;

[0006] The following steps are involved:

[0007] (1) mixing chitosan powder with an organic acid, reacting to obtain a mixed solution I, and centrifuging the mixed solution I to obtain an upper layer of liquid I and a lower layer of solid I;

[0008] (2) mixing the lower solid I obtained in (1) with water to obtain a mixed solution II, dialyzing, and centrifuging to obtain an upper liquid II and a lower solid II;

[0009] (3) subjecting the upper layer liquid II obtained in (2) to layering treatment to obtain a product containing chitosan nanowhiskers and a mixed liquid III;

[0010] (4) subjecting the mixed solution III obtained in (3) to high pressure homogenization to obtain a product containing chitosan nanofibers;

[0011] Specifically, the steps include:

[0012] a) reacting chitosan powder with different organic acids, at different temperatures, for different times, and with different acid contents under certain conditions to obtain a suspension I and calculating the yield;

[0013] b) centrifuging the suspension I to obtain an upper layer of spent acid and a lower layer of solid;

[0014] c) cooling and recrystallizing the upper layer of waste acid to obtain a recyclable organic acid;

[0015] d) diluting the lower layer solid to a certain concentration, dialyzing, and centrifuging to obtain a suspension II;

[0016] e) separating and treating the suspension II to obtain an upper layer of chitosan nano whiskers ChNC and a lower layer of waste liquid solid CSR;

[0017] f) treating the waste liquid solid CSR by a high pressure homogenizer to obtain chitosan nanofibers ChNF;

[0018] The organic acid is selected from at least one of toluenesulfonic acid, oxalic acid and maleic acid;

[0019] The ratio of the mass of the organic acid to the mass of the chitosan powder is 0.6-1.8:1.

[0020] Optionally, the ratio of the mass of the organic acid to the mass of the chitosan powder is any value among 0.6:1, 0.8:1, 1.0:1, 1.2:1, 1.4:1, 1.6:1, 1.8:1, or a range between any two of them.

[0021] The reaction temperature is 80-160°C;

[0022] Optionally, the reaction temperature is any value of 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, or any range therebetween.

[0023] The reaction time is 2 to 12 hours.

[0024] Optionally, the reaction time is any value among 2h, 4h, 6h, 8h, 10h, 12h, or a range between any two of them.

[0025] The centrifugal speed is 10000-15000 rpm;

[0026] Optionally, the centrifugal rotation speed is any value among 10000 rpm, 11000 rpm, 12000 rpm, 13000 rpm, 14000 rpm, 15000 rpm or any range value between two thereof.

[0027] The centrifugation time is 2 to 15 minutes.

[0028] Optionally, the centrifugation time is any value among 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, or a range value between any two of them.

[0029] The upper layer liquid I obtained in (1) can be recovered to obtain the organic acid after cooling and recrystallization.

[0030] The cooling recrystallization is carried out by using ethyl acetate as solvent and performing rotary evaporation at 40-60°C.

[0031] The dialysis time is 4 to 24 hours;

[0032] The water is changed 1 to 4 times during the dialysis.

[0033] The pressure of the high-pressure homogenization treatment is 800 to 12000 bar;

[0034] The high pressure homogenization treatment is performed 1 to 10 times.

[0035] According to another aspect of the present application, there is provided a nano-chitosan prepared by the above-mentioned preparation method, wherein the nano-chitosan comprises chitosan nanofibers and chitosan nanowhiskers.

[0036] The chitosan nanofiber particle size is 400-500nm.

[0037] The particle size of the chitosan nano whisker is 100-220 nm.

[0038] According to another aspect of the present application, there is provided an application of the above-mentioned nano-chitin for use in the fields of biomedicine, chemical industry, food industry, agriculture and microelectronics.

[0039] The beneficial effects of this application include:

[0040] 1) The present application successfully prepares nano-chitosan using low-concentration organic acid, which can be recovered and recycled to reduce environmental pollution.

[0041] 2) The present application realizes the simultaneous recovery of chitosan nanowhiskers and CSR (chitosan solid residue), and obtains chitosan nanofibers by high-pressure homogenization of CSR to minimize chitosan loss and increase total yield.

[0042] 3) The chitosan nanowhiskers and chitosan nanofibers prepared in this application can be applied to polymer reinforcement, food packaging, water treatment, drug delivery, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a Fourier infrared spectrum of chitosan powder and chitosan nanowhiskers in Example 1 of the present application;

[0044] Figure 2 The X-ray diffraction pattern of chitosan powder and chitosan nanowhiskers in Example 1 of the present application;

[0045] Figure 3 This is a transmission electron microscope image of the chitin nanowhiskers in Example 1 of the present application, with a scale of 0.5 μm;

[0046] Figure 4 This is a scanning electron microscope image of the chitosan nanowhiskers in Example 1 of the present application, with a scale of 1 μm. Figure 5 Figure 2 is a graph of the experimental yield and the predicted yield in the regression model. Figure 6 The response surface shows the effect of different process parameters on the ChNC yield. DETAILED DESCRIPTION

[0047] The analysis method in the examples of this application is as follows:

[0048] The chemical structure of chitosan powder and chitosan nanowhiskers was analyzed by Fourier transform infrared spectrometer;

[0049] The crystal structure and crystallinity of chitosan powder and chitosan nanowhiskers were analyzed by X-ray diffraction;

[0050] Thermal analysis was used to analyze the thermal stability of chitosan powder and chitosan nanowhiskers;

[0051] The particle size of chitosan powder and chitosan nanowhiskers was analyzed by laser particle size analyzer.

[0052] The morphology and size of chitosan powder and chitosan nanowhiskers were analyzed using transmission electron microscopy and scanning electron microscopy;

[0053] The Fourier transform infrared spectrometer test conditions are as follows: the prepared chitosan nano whisker sample and potassium bromide are mixed in a ratio of 1:100 by using the KBr tableting method, and ground in an agate mortar for five minutes. The ground powder is poured into a mold and made into a translucent sheet by using a tabletting machine. The infrared spectrometer is set to the transmission mode and the wave number is 400-4000cm -1 Collect signals within the range of

[0054] The X-ray diffraction phase analysis test conditions are as follows: before testing, the material is gently ground in an agate mortar for one minute, then an appropriate amount of sample is spread flat in the groove of the slide, lightly pressed to a flat surface and the slide is placed on the sample holder. ) Irradiate the sample in step scanning mode, set the instrument scanning range to 10°-60°, and the scanning speed to 5°min -1 . The crystallinity index (CrI) was calculated using the Segal empirical formula;

[0055] The particle size test conditions are as follows: the Mastersizer 2000 laser particle size analyzer used is assembled with the Hydro2000S wet accessories, deionized water is used as the dispersed phase, and the particle size distribution of the dispersed particles in the water phase is detected. Before the test, the refractive index is set to 1.53, the stirring speed is 1500rpm, and the sample is ultrasonically treated in advance. First, the blank sample is tested and the background value is subtracted. Then, the sample stored in deionized water is added to the sample pool with a dropper, and the test is started when the intensity value reaches the preset value;

[0056] The thermal analysis test conditions are as follows: a thermogravimetric analyzer is used to record the thermal weight loss curve. 10 mg of sample is weighed in an alumina dry pan, and thermal stability analysis is performed in a nitrogen atmosphere within a temperature range of 25-600°C. During the test, the heating rate is set at 10°C min -1 , nitrogen flow rate was 20 mL min -1 ;

[0057] The transmission electron microscope test conditions are as follows: the morphology and size distribution of the sample are characterized by a transmission electron microscope, and the sample preparation method is the same as the preparation method of the sample in the SEM test water phase. The diameters of 150 particles in the TEM image are measured, and the particle size distribution of nano-chitin is statistically calculated using software;

[0058] The scanning electron microscope test conditions are as follows: the morphology of the sample is observed using a scanning electron microscope, the GB mode is used, and the accelerating voltage is 3.0 kV. A certain amount of sample suspension is taken, the deionized water therein is replaced with anhydrous ethanol, and then the sample liquid is dropped onto the surface of a 300-mesh carbon-coated copper mesh using a disposable dropper. The copper mesh is placed under an infrared lamp to dry, and the sample loaded on the surface of the copper mesh is characterized;

[0059] Example 1

[0060] (1) p-Toluenesulfonic acid and chitosan powder were reacted at a temperature of 130°C, a time of 4 hours, and an acid ratio of 1.2.

[0061] (2) After the reaction is stopped, centrifuge at a speed of 15000 rpm and a centrifugal time of 5 min to obtain the upper acid waste liquid and the lower solid.

[0062] (3) The upper acid waste liquid was concentrated by rotary evaporation at 50°C under vacuum conditions and then cooled and crystallized at room temperature. The lower solid was added with 80 ml of deionized water and transferred to a dialysis bag for 24 hours, during which the water was changed every 12 hours.

[0063] (4) After dialysis is completed, centrifuge again at a speed of 15,000 rpm for 5 min to obtain the upper layer of chitosan nanowhiskers ChNC and the lower layer of waste liquid solid CSR.

[0064] (5) The lower layer of waste liquid solid CSR is homogenized by high pressure to obtain chitosan nanofibers ChNF. The upper layer of chitosan nanowhiskers ChNC is calculated to have a yield of 34.3% by drying method, and the calculation formula is ChNC (%) = M0 / M1*100%, where M0 is the mass of ChNC after drying, and M1 is the mass of added chitosan.

[0065] Figure 1 This is the Fourier infrared spectrum of chitosan powder and chitosan nanowhiskers in Example 1 of the present application; it can be seen from the figure that at 3446cm -1 The stretching vibrations of hydrogen bonds are 3259 and 3106 cm -1 Asymmetric and symmetric stretching vibrations of NH, 1660 and 1620 cm -1 The infrared characteristic peak amide I of α-chitin appeared, proving that the chemical structure of chitin was not affected during the preparation of nano-chitin by acid hydrolysis.

[0066] Figure 2This is the X-ray diffraction pattern of chitosan powder and chitosan nanowhiskers in Example 1 of the present application; it can be seen from the figure that after acid hydrolysis, all peaks appear at the same 2θ value, which indicates that the basic structure of chitosan is retained during the acid hydrolysis process, and the crystallinity of ChNC after acid hydrolysis is slightly improved compared to the raw chitosan, which indicates that the acid hydrolysis method removes the amorphous region of chitosan or the region with incomplete crystallization.

[0067] Figure 3 This is a transmission electron microscope image of the chitosan nanowhiskers in Example 1 of the present application, with a scale of 0.5 μm. It can be seen from the image that the chitosan nanowhiskers after acid hydrolysis treatment are spindle-shaped, indicating that p-toluenesulfonic acid can successfully prepare nanochitosan under certain hydrolysis conditions.

[0068] Figure 4 This is a scanning electron microscope image of chitosan nano whiskers in Example 1 of the present application, with a scale of 1 μm. It can be seen from the figure that it is similar to the transmission electron microscope image, which once again proves that p-toluenesulfonic acid can successfully prepare nano chitosan under certain hydrolysis conditions.

[0069] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing nano-chitin, characterized in that: The nano-chitosan includes chitosan nanofibers and chitosan nanowhiskers; The following steps are involved: (1) mixing chitosan powder with an organic acid, reacting to obtain a mixed solution I, and centrifuging the mixed solution I to obtain an upper layer of liquid I and a lower layer of solid I; (2) mixing the lower solid I obtained in (1) with water to obtain a mixed solution II, dialyzing, and centrifuging to obtain an upper liquid II and a lower solid II; (3) subjecting the upper layer liquid II obtained in (2) to layering treatment to obtain a product containing chitosan nanowhiskers and a mixed liquid III; (4) subjecting the mixed solution III obtained in (3) to high pressure homogenization to obtain a product containing chitosan nanofibers; The organic acid is selected from at least one of toluenesulfonic acid, oxalic acid and maleic acid; The ratio of the mass of the organic acid to the mass of the chitosan powder is 0.6-1.8:

1.

2. The method for preparing nano-chitin according to claim 1, characterized in that: The reaction temperature is 80-160°C; The reaction time is 2 to 12 hours.

3. The method for preparing nano-chitosan according to claim 1, characterized in that: The centrifugal speed is 10000-15000 rpm; The centrifugation time is 2 to 15 minutes.

4. The method for preparing nano-chitosan according to claim 1, characterized in that: The upper layer liquid I obtained in (1) can be recovered to obtain the organic acid after cooling and recrystallization.

5. The method for preparing nano-chitosan according to claim 4, characterized in that: The cooling recrystallization is carried out by using ethyl acetate as solvent and performing rotary evaporation at 40-60°C.

6. The method for preparing nano-chitosan according to claim 1, characterized in that: The dialysis time is 4 to 24 hours; The water is changed 1 to 4 times during the dialysis.

7. The method for preparing nano-chitosan according to claim 1, characterized in that: The pressure of the high-pressure homogenization treatment is 800 to 12000 bar; The high pressure homogenization treatment is performed 1 to 10 times.

8. A nano-chitosan prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The nano-chitosan includes chitosan nanofibers and chitosan nanowhiskers.

9. The nano-chitosan according to claim 8, characterized in that: The chitosan nanofiber particle size is 400-500nm. The particle size of the chitosan nano whisker is 100-220nm.

10. An application of the nano-chitosan according to any one of claims 8 or 9, characterized in that: Used in biomedicine, chemical industry, food industry, agriculture and microelectronics.

Citation Information

Patent Citations

  • Chitin nano crystal whisker, chitin nanofiber and preparation method thereof

    CN106868631A